GROWTH FACTOR AND ADIPOKINE RECEPTORS IN PATHOGENESIS AND PROGNOSIS OF ENDOMETRIAL CANCER IN PATIENTS WITH METABOLIC SYNDROME - N. V. Yunusova; I. V. Kondakova; L. А. Kolomiets; А. L. Chernyshova; Е. V. Shanshashvili (Сибирский онкологический журнал)
The role of growth factor receptors (insulin-like growth factor and transforming growth factor-beta) and adipokine receptors (leptin and adiponectin) in pathogenesis of endometrial cancer under conditions of metabolic syndrome is discussed. Cyclooxygenase-2 is an effector of signaling pathways activated by growth factors and cytokines. The detailed study of the mechanisms involving these proteins in pathogenesis of endometrial cancer in patients with metabolic syndrome and search for new biological prognostic markers appear to be promising.